Immune escape and survival mechanisms in circulating tumor cells of colorectal cancer - Steinert, Gunnar; Schölch, Sebastian; Niemietz, Thomas; Iwata, Naoki; García, Sebastián A.; Behrens, Bianca; Voigt, Anita Yvonne; Kloor, Matthias; Benner, Axel; Bork, Ulrich; Rahbari, Nuh N.; Büchler, Markus W.; et al. (Cancer research, 2014)
The prognosis of colorectal cancer is closely linked to the occurrence of distant metastases. Systemic dissemination is most likely caused by circulating tumor cells (CTC). Despite the fundamental role of CTC within the metastatic cascade, technical obstacles have so far prevented detailed genomic and, in particular, phenotypic analyses of CTC, which may provide molecular targets to delay or prevent distant metastases. We show here a detailed genomic analysis of single colorectal cancer-derived CTC by array comparative genomic hybridization (aCGH), mutational profiling, and microsatellite instability (MSI) analysis. Furthermore, we report the first gene expression analysis of manually selected colorectal cancer-derived CTC by quantitative real-time PCR (qRT-PCR) to investigate transcriptional changes, enabling CTC to survive in circulation and form distant metastases.
Gesehen am 22.09.2020